Dose planning objectives in anal canal cancer IMRT: the TROG ANROTAT experience. Issue 2 (12th February 2015) - Brown, Elizabeth; Cray, Alison; Haworth, Annette; Chander, Sarat; Lin, Robert; Subramanian, Brindha; Ng, Michael
Abstract Introduction Intensity modulated radiotherapy (IMRT) is ideal for anal canal cancer (ACC), delivering high doses to irregular tumour volumes whilst minimising dose to surrounding normal tissues. Establishing achievable dose objectives is a challenge. The purpose of this paper was to utilise data collected in the Assessment of New Radiation Oncology Treatments and Technologies (ANROTAT) project to evaluate the feasibility of ACC IMRT dose planning objectives employed in the Australian situation. Methods Ten Australian centres were randomly allocated three data sets from 15 non‐identifiable computed tomography data sets representing a range of disease stages and gender. Each data set was planned by two different centres, producing 30 plans. All tumour and organ at risk (OAR) contours, prescription and dose constraint details were provided. Dose–volume histograms (DVHs) for each plan were analysed to evaluate the feasibility of dose planning objectives provided. Results All dose planning objectives for the bone marrow (BM) and femoral heads were achieved. Median planned doses exceeded one or more objectives for bowel, external genitalia and bladder. This reached statistical significance for bowel V30 (P = 0.04), V45 (P < 0.001), V50 (P < 0.001), external genitalia V20 (P < 0.001) and bladder V35 (P < 0.001), V40 (P = 0.01). Gender was found to be the only significant factor in the likelihood of achieving the bowel V50 (P = 0.03) and BM V30 constraints (P = 0.04). Conclusion The dose planning objectives used in the ANROTAT project provide a good starting point for ACC IMRT planning. To facilitate clinical implementation, it is important to prioritise OAR objectives and recognise factors that affect the achievability of these objectives.